ANALISIS KINERJA AGRIBISNIS UDANG VANNAMEI (STUDI KASUS DI DESA DUKUHTUNGGAL KECAMATAN GLAGAH KABUPATEN LAMONGAN) - Suyoto Suyoto; Syarif Imam Hidayat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to analyze the performance of agribusiness and formulate strategies for strengthening the performance of vannamei shrimp. This research is a quantitative research with a descriptive approach with survey techniques, and identifies problems and constraints. Determination of strengthening strategy formulation with strength field analysis (FFA).      The results of the performance measurement are that the condition of the seeds is of poor quality and the price is expensive, the equipment is limited and still relatively expensive, the scarcity of fertilizers often occurs in the growing season and the price is relatively high, the wages of daily laborers are still relatively high. Traditional plus cultivation technology, which depends on survival stocked prawns. Handling the results is focused on the management at the collectors, from washing to the storage process in a storage tank with ice only. Lack of information on shrimp prices in the market due to ineffective information media. Fishery education is lacking, there are no human resource development institutions, cooperatives and lack of research, inlet and outlet channels are still connected.      The strategy for strengthening agribusiness is to mobilize the group as a vehicle for coordination, synergy and driving force for the development of vannamei shrimp agribusiness. Integrate and synchronize government policies by fulfilling the availability of fertilizers according to need, disease-free and disease-resistant (SPR) shrimp seeds, procurement of production equipment equipment that has been adapted to production needs, increasing the capacity of the farmer's workforce through training activities, OJT , seminars, regular workshops. Focus on primary product, namely vannamei shrimp with more advanced cultivation systems and technology guided by CBIB. Developing processed products made from vannamei shrimp, quality management training, HACCP and GMP, forming processing and marketing groups and stimulating the construction of fishery product processing plants. Develop entrepreneurial skills by relying on the principles of business groups that lead to a modern system. Provide good and easy-to-access information media. Capital assistance for businesses and support for adequate infrastructure construction services, expansion of communication and transportation networks, and strengthening of pokdakkan bookkeeping, strengthening between government institutions, private institutions and microfinance with pokdakkan in order to find investors to build factories and fishery cooperatives.